The IFMIF-DONES Irradiation Modules - Arbeiter, F.; Wiącek, U.; Brañas, B.; Gordeev, S.; Kupferschmitt, A.; Qiu, Y.; Serikov, A.; Zhou, G.; Kotula, J.; Arranz, F.; Mota, F.; Ortiz, M.I.; et al. (Nuclear fusion, 2025)
The IFMIF-DONES Irradiation Modules consist of a set of systems designed to be tested in the IFMIF-DONES facility and which are thought to produce, in the future, an extensive, qualified and unique set of fusion-like irradiated experimental data associated to the materials and the structures to be used in specific breeding blankets (BBs) that are currently under consideration for the EU DEMO fusion reactor. The irradiation conditions (neutron fluence and spectra) at the position of the IFMIF-DONES Irradiation Modules inside the test cell, will be comparable to that expected as reference in the most exposed zones of the EU DEMO reactor. Nevertheless, medium and low flux regions will be also available. In this work, an introduction to the description of the main IFMIF-DONES Irradiation Modules is given. Particularly, the following 5 modules are described: the (IFMIF-DONES) High Flux Test Module, HFTM, tailored to powerful irradiate structural materials such as small specimens of Eurofer, the (IFMIF-DONES) Start-up Monitoring Module, STUMM, designed to monitor the radiation fields produced just behind the neutron source, under transient and steady state conditions, the (IFMIF-DONES) Blanket Functional Material Module, BLUME, which is a representative section of the Helium Cooled Pebble Bed (HCPB) blanket breeder zone, the (IFMIF-DONES) Liquid Breeder Validation Module, LBVM, for the irradiation of functional materials such as PbLi and anti-corrosion/anti-permeation barriers, and the (IFMIF-DONES) Tritium Release Test Module, TRTM, which is defined for the irradiation of lithium ceramic pebble beds associated to the HCPB BB.